Dyke-Davidoff-Masson syndrome: A study of clinicoradiological variability in hemiplegia, hemiatrophy and epilepsy patients - Amita Bhargava; Bharat Bhushan; Gaurav Kasundra; Khichar Shubhakaran; S Pujar Guruprashad; Banakar Basavaraj (Wolters Kluwer Medknow Publications, 2014)
Context: Clinicoradiological variability expansion in Dyke-Davidoff-Masson syndrome (DDMS) or hemiplegia, hemiatrophy and epilepsy (HHE) patients. Aims: To explore clinicoradiological features, associated abnormalities and refractoriness issues to antiepileptic drugs (AED) on such kind of epilepsy syndrome. Settings and Design: Prospective and retrospective observational hospital based cohort study. Materials and Methods: Thirty-two patients of HHE were enrolled and interviewed. They were divided into 4 groups congenital versus acquired and seizure control group (SCG) versus seizure refractory group (SRG). We used Naranjo adverse drug reaction (ADR) probability scale for analyzed phenytoin and other drugs adverse reaction. All patients underwent clinicoradiological examination, electroencephalograms, magnetic resonance imaging for parenchymal and skeletal changes. Statistical Analysis Used: Fisher's exact and Student's t-test applied for P value. Results: A total of 32 patients (21 males, 11 females) out of 1182 epilepsy patients were enrolled with mean age of 26.84 ± 9.71 (range: 8-42) years. Twenty-eight patients presented with DDMS, three Rasmussen encephalitis and two HHE syndromes. Congenital type and seizure refractory groups were common presentation. Left lateralization with holo-hemispheric atrophy, cerebellar atrophy, calvarial thickening with frontal sinus hyperpneumatization were significant (P < 0.05) magnetic resonance imaging (MRI) findings. Epileptiform activity was concordant to lesion. Phenytoin adverse effects were significantly (P < 0.03) associated with HHE patients. Remarkable findings of our study included cerebral hemispheric plus cerebellar atrophy (28.12%), hippocampal sclerosis (16%), dystonia, hemiparkinsonism, mirror movement and Dandy-Walker syndrome (DWS). Conclusions: DDMS/HHE can present protean clinicoradiological manifestation, cerebellar atrophy, hippocampal sclerosis and phenytoin intolerance may be one of them.